Hydroperitoneum: A complication of mini PCNL in pediatric age group? -A case report - Farheen Batool; Waqar Ahmed Memon; Javed Altaf Jat; Shewak Ram; Taimoor Jatoi; Abdul Qayoom Ghangro (LIAQUAT MEDICAL RESEARCH JOURNAL, 2021)
Abstract Renal stones constitute 40% of renal disorders in Pakistan with silent stones constituting up to 3%. Nephrolithotomy and Pyelolithotomy were the only surgical options available for the treatment of large renal stones, with high rate of complications. Percutaneous nephrolithotomy (PCNL) has now become the mainstay of treatment for large renal stones over the past 30 years. Recent advances in equipment and technology has made PCNL the gold standard for this disease, resulting in removal of stones with shorter recovery time and decreased morbidity and mortality, and with few complications Case Discussion A boy aged 13 years, underwent mini PCNL for treatment of left side renal stone causing hydronephrosis, previously evaluated by KUB X-Rray and non contrast CT scan. His retrograde-percutanous access to the collecting system was done under fluoroscopic guidance. At the end of procedure, patient revealed taut and distended abdomen. Aspiration revealed presence of intraperitoneal fluid. Patient was effectively treated with immediate placement of abdominal drain with improvement of clinical presentation Conclusion Hydroperitoneum is a rare complication of conventional PCNL. Based on our experience and review of published literature, our case of hydroperitoneum after mini PCNL, is the first of its kind. A high degree of sensitivity and knowledge of this complication during PCNL in children would help identify and manage this complication in future. We recommend examination of abdomen post-PCNL in every child before he/she is brought out of anesthesia.